1985
DOI: 10.1007/bf00339562
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and non-reversible enlargement of cerebrospinal fluid spaces in anorexia nervosa

Abstract: Brain CT studies of 35 patients with anorexia nervosa confirmed the observations of other authors: cerebral dystrophic changes correlate with weight loss and the reversibility of these changes also correlates with the normalization of body weight. Other corroborated facts are: the most numerous and most pronounced enlargements are of the cortical sulci and the interhemispheric fissure, moderate widening affects the ventricles and the rarest and most insignificant changes are those of the cerebellum. The revers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 46 publications
3
65
0
Order By: Relevance
“…Neuroimaging studies with CT reported cerebral atrophy and enlarged ventricles in ill AN (98)(99)(100)(101)(102)(103)(104)(105)(106). In BN similar but less pronounced structural brain abnormalities were reported (107) and may have been related to a chronic dietary restriction.…”
Section: Brain Structurementioning
confidence: 74%
“…Neuroimaging studies with CT reported cerebral atrophy and enlarged ventricles in ill AN (98)(99)(100)(101)(102)(103)(104)(105)(106). In BN similar but less pronounced structural brain abnormalities were reported (107) and may have been related to a chronic dietary restriction.…”
Section: Brain Structurementioning
confidence: 74%
“…Possibly the most im- portant mechanism for undernutrition-induced brain changes could be hypercortisolism (Heinz, Martinez, & Haenggeli, 1977) and/or the decreased intravascular colloid pressure due to loss of serum protein, with subsequent movement of water into the CSF space (Artmann, Grau, Adelmann, & Schleiffer, 1985;Hoffmann et al, 1989a).…”
Section: Discussionmentioning
confidence: 99%
“…While it is well known that ill AN subjects have reduced cortical volume (Ellison and Fong, 1998) and increased ventricular volume (Golden et al, 1996;Swayze et al, 1996;Katzman et al, 1996), it remains uncertain whether such brain volume reductions and enlargement of CSF spaces persist in the recovered state (Artmann et al, 1985;Swayze et al, 2003). Some studies showed that weightrecovered AN have significantly greater CSF volumes and smaller gray matter volumes than healthy control women Katzman et al, 1997, Krieg et al, 1988.…”
Section: Only Rec An Have Reduced [mentioning
confidence: 99%